Hubungan Keikutsertaan Kelas Ibu Hamil Resiko Tinggi Dengan Jenis Persalinan - Sri Wahyuni; Astri Wahyuningsih; Dhea Permata Sari (Universitas Muhammadiyah Klaten, 2021)
Government programs in reducing maternal mortality by implementing high-risk pregnant women classes, with the existence of high-risk pregnant women class activities are expected to increase the number of normal deliveries, reduce the risk of childbirth and reduce maternal mortality. The purpose of this study was to determine the relationship between class participation of high-risk pregnant women and the type of delivery in the Trucuk II Public Health Center. This research method is correlational descriptive with cross sectional approach. In this study, the population used were all high-risk pregnant women in the Trucuk II Klaten health center for the period 1 July - 30 December 2019 as many as 134 respondents. The number of research samples is 34 respondents. Sampling with simple random sampling technique. The instrument used is a documentation sheet. Analysis of the data using the Chi-square test calculation. The results of the study, namely the participation of high-risk pregnant women with the type of delivery, showed that of the 34 respondents, most of them did not follow as many as 21 (62%) with vaginal delivery, 15 respondents (68.2%) per abdominal 7 respondents (31.8%). . Respondents with the following categories were 13 (38%) with vaginal delivery 8 respondents (66.7%) per abdominal 4 respondents (33.3%).